Records Management Strategies in Secondary Schools in Esan-West Local Government Area of Edo State, Nigeria - Omigie, Christopher Agbeniaru; Makinde, Theresa Osasu; Oboite, Antony Solomon (Communicate: Journal of Library and Information Science, 2023)
This study examined the Records Management Strategies in Secondary Schools in Esan-West Local Government Area of Edo State, Nigeria. The study adopted the descriptive research survey design. The sample of the study was 136 respondents made up of 12 school principals, 114 teachers and 10 administrative staff in the 12 public senior secondary schools in the local government area. The data collected by the means of questionnaire were analyzed using frequency counts and simple percentages. Results revealed the types of records that were available in the schools; the storage facilities of obsolete cupboards, open shelves and drawers; the poor records management strategies with very low impact of records management in the schools’ administration; various challenges, among others were also uncovered. The paper suggested the integration of open sources and cloud-based Computer School Records Management System (CSRMS) using software like Edmatix, Fefena, Alma, Gradelink SIS, Class 365, iGradeplus, Fekara, Gibbon, etc, which are comprehensive with fine interface designs for school records system.